physicscatalyst.com logo




Continuity and Differentiability NCERT Solutions for Class 12 Maths Exercise 5.2




In this page we have Continuity and Differentiability NCERT Solutions for Class 12 Maths Exercise 5.2 . Hope you like them and do not forget to like , social share and comment at the end of the page.

Differentiate the function with respect to x

Question 1
$\ sin (x^{2}+5)$
Solution
The given function is $f(x)=\ sin (x^{2}+5)$
We can see that $f$ is a composite function which can be written in the form of two composite function $u$ and $v$.
$u(x)=x^{2}+5$
$v(t)=\sin t$
$(vou)(x)=v(u(x))=v(x^{2}+5)=\sin (x^{2}+5)=f(x)$ put $t=(x^{2}+5)$
$\frac{\mathrm{d} v}{\mathrm{d} t}=\cos t$
And $\frac{\mathrm{d} t}{\mathrm{d} x}=2x$
By chain rule ,
$\frac{\mathrm{d} f}{\mathrm{d} x}=\frac{\mathrm{d} v}{\mathrm{d} t}\times \frac{\mathrm{d} t}{\mathrm{d} x}$
$\frac{\mathrm{d} f}{\mathrm{d} x}=\cos t \times (2x)$
And we know $t=x^{2}+5$
Thus $\frac{\mathrm{d} f}{\mathrm{d} x}=(2x)\cos x^{2}+5$


Question 2
$\cos (\sin x)$
Solution
Let $f(x)=\cos (\sin x)$
We can see that $f$ is a composite function which can be written in the form of two composite function $u$ and $v$.
$u(x)=\sin x\; \; and\; \; v(t)=\cos t$
$(vou)(x)=v(u(x))=v(\sin x)=\cos (\sin x)=f(x)$
Put $t=u(x)=\sin x$
$therefore,\; \frac{\mathrm{d} v}{\mathrm{d} t}=\frac{\mathrm{d} (\cos t)}{\mathrm{d} t}=-\sin t = -\sin(\sin x)$
$\frac{\mathrm{d} t}{\mathrm{d} x}=\frac{\mathrm{d} (\sin x)}{\mathrm{d} x}=\cos x$
By chain rule ,
$\frac{\mathrm{d} f}{\mathrm{d} x}=\frac{\mathrm{d} v}{\mathrm{d} t}\times \frac{\mathrm{d} t}{\mathrm{d} x}$
$\frac{\mathrm{d} f}{\mathrm{d} x}=-\sin (\sin x)\times \ cos x=-\cos x\sin (\sin x)$

Question 3
$\sin (ax+b)$
Solution

Let $f(x)=\sin (ax+b)$
We can see that $f$ is a composite function which can be written in the form of two composite function $u$ and $v$.
$u(x)=ax+b\; \; and\; \; v(t)=\sin t$
$(vou)(x)=v(u(x))=v(ax+b)=\sin (ax+b)=f(x)$
Put $t=u(x)=ax+b$
$therefore,\; \frac{\mathrm{d} v}{\mathrm{d} t}=\frac{\mathrm{d} (\sin t)}{\mathrm{d} t}=\cos t = \cos(ax+b)$
$\frac{\mathrm{d} t}{\mathrm{d} x}=\frac{\mathrm{d} (ax+b)}{\mathrm{d} x}=a$
By chain rule ,
$\frac{\mathrm{d} f}{\mathrm{d} x}=\frac{\mathrm{d} v}{\mathrm{d} t}\times \frac{\mathrm{d} t}{\mathrm{d} x}$
$\frac{\mathrm{d} f}{\mathrm{d} x}=a\times \ cos (ax+b)$

Question 4
$\sec (\tan (\sqrt{x}))$
Solution

Let $f(x)=\sec (\tan (\sqrt{x}))$
We can see that $f$ is a composite function which can be written in the form of three composite function $u$,$v$ and $w$.
$u(x)=\sqrt{x}\; \; v(t)=\tan t\; \; and w(s)=\sec s$
$(wovou)(x)=w[v(u(x))]=w[v(\sqrt{x})]=w[\tan( \sqrt{x})]=\sec (\tan (\sqrt{x}))=f(x)$
Put $s=v(t)=\tan t and t=u(x)=\sqrt{x}$
then ,$\frac{\mathrm{d} w}{\mathrm{d} s}=\frac{\mathrm{d} (\sec s)}{\mathrm{d} s}=\sec s\tan s$
Now $s=\tan t$ $=\sec(\tan t). \tan (\tan t)$
$=\sec(\tan \sqrt{x}). \tan (\tan \sqrt{x})$
$\frac{\mathrm{d} s}{\mathrm{d} t}=\frac{\mathrm{d} (\tan t)}{\mathrm{d} t}=\sec ^{2}t=\sec ^{2}\sqrt{t}$
$\frac{\mathrm{d} t}{\mathrm{d} x}=\frac{\mathrm{d} \sqrt{x}}{\mathrm{d} x}=\frac{\mathrm{d} (x^{\frac{1}{2}})}{\mathrm{d} x}=\frac{1}{2}.x^{\frac{1}{2}-1}=\frac{1}{2\sqrt{x}}$
By chain rule ,
$\frac{\mathrm{d} t}{\mathrm{d} x}=\frac{\mathrm{d} w}{\mathrm{d} s}\times \frac{\mathrm{d} s}{\mathrm{d} t}\times \frac{\mathrm{d} t}{\mathrm{d} x}$
=$\sec (\tan\sqrt{x}).\tan (\tan\sqrt{x})\times \sec ^{2} \sqrt{x}\times \frac{1}{2\sqrt{x}}$
=$\frac{\sec ^{2}\sqrt{x}.\sec (\tan \sqrt{x}.\tan (\tan \sqrt{x}))}{2\sqrt{x}}$

Question 5
$\frac{\sin (ax+b)}{\cos(cx+b)}$
Solution
The given function is $f(x)=\frac{\sin (ax+b)}{\cos(cx+b)}= \frac{g(x)}{h(x)}$,
where $g(x)= \sin (ax+b) $ and $h(x)=\cos (cx+d)$
Differentiation of f(x) will be given by quotient formula
$\frac{\mathrm{d} f}{\mathrm{d} x}=\frac{g^{'}h-h^{'}g}{h^{2}}$
So we need to find the differentiation of the function g(x) and h(x)
We can use the same technique of chain rule here
Consider $g(x)=\sin (ax+b)$
Here $g$ is a composite function which can be written in the form of two composite function $u$ and $v$.
$u(x)=ax+b\; \; v(t)=\sin t$
$(vou)(x)=v(u(x))=v(ax+b)=\sin (ax+b)]=g(x)$
Put $t=u(x)=ax+b$
$\frac{\mathrm{d} v}{\mathrm{d} t}=\frac{\mathrm{d} (\sin t)}{\mathrm{d} t}=\cos t=\cos (ax+b)$
$\frac{\mathrm{d} t}{\mathrm{d} x}=\frac{\mathrm{d} (ax+b)}{\mathrm{d} x}=a$
By chain rule ,
$g^{‘}=\frac{\mathrm{d} g}{\mathrm{d} x}=\frac{\mathrm{d} v}{\mathrm{d} t}\times \frac{\mathrm{d} t}{\mathrm{d} x}=\cos (ax+b).a=a \cos (ax+b)$
Consider $h(x)=\cos (cx+d)$
Here $h$ is a composite function which can be written in the form of two composite function $p$ and $q$.
$p(x)=cx+d\; \; q(y)=\cos y$
$(qop)(x)=q(p(x))=q(cx+d)=\cos (cx+d)]=h(x)$
Put $y=p(x)=cx+d$
$\frac{\mathrm{d} q}{\mathrm{d} y}=\frac{\mathrm{d} (\cos y)}{\mathrm{d} y}=-\sin y=-\sin (cx+d)$
$\frac{\mathrm{d} y}{\mathrm{d} x}=\frac{\mathrm{d} (cx+d)}{\mathrm{d} x}=c$
By chain rule ,
$h^{‘}=\frac{\mathrm{d} h}{\mathrm{d} x}=\frac{\mathrm{d} q}{\mathrm{d} y}\times \frac{\mathrm{d} y}{\mathrm{d} x}=-\sin (cx+d).c=-c \sin (cx+d)$
Therefore Differentiation of function f(x) will be given by
$\frac{\mathrm{d} f}{\mathrm{d} x}=\frac{a\cos (ax+b).\ cos (cx+d)-\sin (ax+b)(-\sin(cx+d))}{[\cos(cx+d)]^{2}}$
=$\frac{a\cos (ax+b)}{\ cos (cx+d)}+c\sin (ax+b).\frac{\sin (cx+d)}{\cos (cx+d)}\times \frac{1}{\cos (cx+d)}$
=$a\cos (ax+b)\ sec (cx+d)+c\sin (ax+b).\tan (cx+d).\sec (cx+d)$

Question 6
$\cos x^{3}.\sin ^{2}(x^{5})$
Solution
The given function is $f(x)=\cos x^{3}.\sin ^{2}(x^{5})$
By Multiplication(Product) Formula of differentiation
$\frac{\mathrm{d} f}{\mathrm{d} x}=\frac{\mathrm{d} }{\mathrm{d} x}\left [ \cos x^{3}.\sin ^{2}(x^{5}) \right ]$
$=\sin ^{2}(x^{5})\times \frac{\mathrm{d} }{\mathrm{d} x}\cos x^{3}+\cos x^{3}\times \frac{\mathrm{d} }{\mathrm{d} x}\sin ^{2}(x^{5})$
=$\sin ^{2}(x^{5})\times (-\sin x^{3})\times \frac{\mathrm{d} }{\mathrm{d} x}(x^{3})+\cos x^{3}\times 2\sin (x^{5})\times \frac{\mathrm{d} }{\mathrm{d} x}\left [ \sin (x^{5}) \right ]$
$=-\sin x^{3}.\sin ^{2}(x^{5}) \times 3x^{2}+2\sin (x^{5}).\cos x^{3}.\cos x^{5}\frac{\mathrm{d} }{\mathrm{d} x} (x^{5})$
$=-\sin x^{3}.\sin ^{2}(x^{5}) \times 3x^{2}+2\sin (x^{5}).\cos x^{3}.\cos x^{5}\times 5x^{4}$
$=10x^{4}\sin x^{5}.\cos x^{3}.\cos x^{5}\times -3x^{2}\sin x^{3}.\sin ^{2}(x^{5} )$




Question 7
$2\sqrt{\cot (x^{2})}$
Solution
The given function is $2\sqrt{\cot (x^{2})}$
$\frac{\mathrm{d} }{\mathrm{d} x}2\sqrt{\cot (x^{2})}$ $=2.\frac{1}{2\sqrt{\cot (x^{2})}}\times \frac{\mathrm{d} }{\mathrm{d} x}\left [ \cot (x^{2}) \right ]$ ( We use the chain rule here)
$=\sqrt{\frac{\sin (x^{2})}{\cos (x^{2})}}\times -cosec^{2} (x^{2})\times \frac{\mathrm{d} }{\mathrm{d} x}(x^{2})$ ( We use the chain rule here)
$=-\sqrt{\frac{\sin (x^{2})}{\cos (x^{2})}}\times \frac{1}{\sin ^{2(x^{2})}}\times(2x)$
$=\frac{-2x}{\sqrt{\cos (x^{2})}\sqrt{\sin (x^{2})}\sin (x^{2})}$
$=\frac{-2\sqrt{2}x}{\sin (x^{2})\sqrt{\sin 2(x^{2})}}$

Question 8
$\cos\sqrt{x}$
Solution
The given function $f(x)$ is $\cos\sqrt{x}$.
We can see that $f$ is a composite function which can be written in the form of two composite function $u$ and $v$.
$u(x)=\sqrt{x}$
And $v(t)=\cos t$
$(vou)(x)=v(u(x))$
$=v(\sqrt{x})$
$=\cos (\sqrt{x})$
put $t=u(x)=\sqrt{x}$
Then, $\frac{\mathrm{d} t}{\mathrm{d} x}=\frac{\mathrm{d} }{\mathrm{d} x}(\sqrt{x})=\frac{\mathrm{d} }{\mathrm{d} x}(x^{\frac{1}{2}})=\frac{1}{2}x^{-\frac{1}{2}}$
$=\frac{1}{2\sqrt{x}}$
And, $\frac{\mathrm{d} v}{\mathrm{d} t}=\frac{\mathrm{d} }{\mathrm{d} t}(\cos t)=-\sin t$
$=-\sin (\sqrt{x})$
By chain rule we have,
$\frac{\mathrm{d} v}{\mathrm{d} x}=\frac{\mathrm{d} v}{\mathrm{d} t}.\frac{\mathrm{d} t}{\mathrm{d} x}$.
$=-\sin (\sqrt{x}).\frac{1}{2\sqrt{x}}$
$=-\frac{1}{2\sqrt{x}}\sin (\sqrt{x})$
$=-\frac{\sin (\sqrt{x})}{2\sqrt{x}}$

Question 9
Prove that the function f given by $f(x)=\left | x-1 \right |,x\in \mathbb{R}$, is not differentiable at $x=1$
Solution
The given function is $f(x)=\left | x-1 \right |,x\in \mathbb{R}$.
It is known that a function $f$ is differentiable at a point $x=c$ in its domain if the right hand limit and the left hand limit are finite and equal.
To check the differentiability of the given function at x=1,
The right hand and the left hand limits where x=c are
$\lim_{h \to 0^{+}}\frac{f(c+h)-f(c)}{h}$ and $\lim_{h \to 0^{-}}\frac{f(c+h)-f(c)}{h}$
Considering the right hand limit of the given function at x=1
$\lim_{h \to 0^{+}}\frac{f(1+h)-f(1)}{h}$
$=\lim_{h \to 0^{+}}\frac{\left | 1+h-1 \right |-\left | 1-1 \right |}{h}$
$=\lim_{h \to 0^{+}}\frac{\left | h \right |-\left | 0 \right |}{h}$
$=\lim_{h \to 0^{+}}\frac{h}{h}$
$=1$
Considering the left hand limit of the given function at x=1
$\lim_{h \to 0^{-}}\frac{f(1+h)-f(1)}{h}$
$=\lim_{h \to 0^{-}}\frac{\left | 1+h-1 \right |-\left | 1-1 \right |}{h}$
$=\lim_{h \to 0^{-}}\frac{\left | h \right |-\left | 0 \right |}{h}$
$=\lim_{h \to 0^{-}}\frac{-h}{h}$
$=-1$
Since the left and right hand limits of f at x = 1 are not equal, f is not differentiable at x = 1

Question 10
Prove that the greatest integer function defined by $f(x)=\left [ x \right ], 0<x<3$ is not differentiable at x = 1 and x = 2.
Solution

The function f is $f(x)=\left [ x \right ], 0<x<3$
It is known that a function f is differentiable at a point $x=c$ in its domain if both the left hand and the left hand limit are equal
$\lim_{h \to 0^{+}}\frac{f(c+h)-f(c)}{h}$ and $\lim_{h \to 0^{-}}\frac{f(c+h)-f(c)}{h}$ are finite and equal.
To check the differentiability of the given function at $x=1$, consider the right hand limit of f at $x=1$
$\lim_{h \to 0^{+}}\frac{f(1+h)-f(1)}{h}$
$\lim_{h \to 0^{+}}\frac{\left [ 1+h \right ]-\left [ 1 \right ]}{h}$
$=\lim_{h \to 0^{+}}\frac{1-1}{h}$
$=\lim_{h \to 0^{+}}\frac{1-1}{h}=\lim_{h \to 0^{+}}(0)=0$
Now consider the left hand limit of f at $x=1$
$\lim_{h \to 0^{-}}\frac{f(1+h)-f(1)}{h}$
$\lim_{h \to 0^{-}}\frac{\left [ 1+h \right ]-\left [ 1 \right ]}{h}$
$=\lim_{h \to 0^{-}}\frac{0-1}{h}$
$=\lim_{h \to 0^{-}}\frac{-1}{h}=\infty $
Since left hand and the right hand limit of f at x=1 are not equal, f is not differentiable at x=1.
Now to check the differentiability of the given function at x=2,
consider the left hand limit at x=2.
$\lim_{h \to 0^{-}}\frac{f(2+h)-f(2)}{h}$
$\lim_{h \to 0^{-}}\frac{\left [ 2+h \right ]-\left [ 2 \right ]}{h}$
$=\lim_{h \to 0^{-}}\frac{1-2}{h}$
$=\lim_{h \to 0^{-}}\frac{-1}{h}=\infty $
Now consider the right hand limit of f at $x=2$
$\lim_{h \to 0^{+}}\frac{f(2+h)-f(2)}{h}$
$\lim_{h \to 0^{+}}\frac{\left [ 2+h \right ]-\left [ 2 \right ]}{h}$
$=\lim_{h \to 0^{+}}\frac{2-2}{h}$
$=\lim_{h \to 0^{+}}\frac{0}{h}=\lim_{h \to 0^{+}}(0)=0$
Since the left and right hand limits of f at x = 2 are not equal, f is not differentiable at x = 2



 


Related Topics


link to this page by copying the following text


Go back to Class 12 Main Page using below links
Class 12 Maths Class 12 Physics Class 12 Chemistry Class 12 Biology